College accounting. Chapters 15-28, with working papers - Koerber, Kenneth A. (Homewood, IL : Irwin, 1992)
"College Accounting is intended for use at the undergraduate level. The text and its supplements are designed to provide entry-level students with a complete foundation in general financial accounting.
Includes index.
English text.
Keywords: Accounting